2018
DOI: 10.18632/oncotarget.24735
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcomes of women with ovarian metastases of colorectal cancer treated with oophorectomy with respect to their somatic mutation profiles

Abstract: We clarified the clinical prevalence of ovarian metastases from colorectal cancers (CRCs) in 296 female patients with CRC and evaluated clinical outcomes with relation to their mutational profiles, such as BRAF/KRAS mutation and microsatellite instability (MSI) status. The female CRCs were categorised into three subsets: CRCs with ovarian metastases [6.4% (n = 19), 5-year overall survival (OS) = 24.7%], CRCs with extra-ovarian metastases only [32.4% (n = 96), 5-year OS = 34.5%] and CRCs without any recurrence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 31 publications
2
25
1
Order By: Relevance
“…The level of methylation is targetable by drugs, 34 and discrepancies in methylation between primary and metastatic tumors have been reported. 35 Consistent with this assumption, we found no discrepancies in MSIhigh tumors caused by germline mutations of MMR genes, whereas one patient with a MLH1 promoter 36 and worse prognosis. 36,37 Specifically, 2 patients in this study with MSI-high primary tumors had metastasis to 2 sites, and only the peritoneal metastasis showed MSS, whereas other metastases remained MSI-high.…”
Section: Discussionsupporting
confidence: 83%
“…The level of methylation is targetable by drugs, 34 and discrepancies in methylation between primary and metastatic tumors have been reported. 35 Consistent with this assumption, we found no discrepancies in MSIhigh tumors caused by germline mutations of MMR genes, whereas one patient with a MLH1 promoter 36 and worse prognosis. 36,37 Specifically, 2 patients in this study with MSI-high primary tumors had metastasis to 2 sites, and only the peritoneal metastasis showed MSS, whereas other metastases remained MSI-high.…”
Section: Discussionsupporting
confidence: 83%
“…Long-term survival can be attained in 20%-50% of patients who undergo complete resection [3]. The clinical prevalence of ovarian metastases among patients with CRC was 6.4%, and 5-year OS for those with ovarian and extra-ovarian metastases was 24.7% and 34.5%, respectively (difference not significant) [4]. OS was longer if surgical resection of ovarian metastases was performed, compared with chemotherapy alone (43.1 vs. 17.0 months) [5].…”
Section: Introductionmentioning
confidence: 91%
“…On the swine models, the intraoperative CLI effectively guided the resection of the metastasis in the bladder and the ovary. Although the CRC metastasis in the bladder or ovary is not in the majority , the feasibility of the intraoperative CLI was proved by the experimental data. The in vivo results on the animals also showed that the intraoperative CLI provided an efficient approach to evaluate the tumor resection quality accurately (Figures , quantitative results).…”
Section: Discussionmentioning
confidence: 99%
“…The feasibility of the intraoperative CLI was also investigated with the metastatic CRC on the swine models. Pseudotumors were established in bladder and ovary, which are two adjacent organs that probably involved by CRC in the clinic . 18 F‐FDG of 0.37 MBq was used to simulate metastatic CRC in the bladder, and 0.29 MBq 18 F‐FDG was used in the ovary.…”
Section: Methodsmentioning
confidence: 99%